PERHITUNGAN NILAI POROSITAS DAN PERMEABILITAS DALAM PENGUKURAN DISTRIBUSI PORI MENGGUNAKAN METODE MERCURY INJECTION CAPILLARY PRESSURE - Aulia Huda Pinandita; Abdullah Rizky Agusman; Angelic Leatemia (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to calculate the porosity and permeability values ​​of rocks through pore distribution analysis using the Mercury Injection Capillary Pressure (MICP) method. This method works based on the principle of capillary pressure, where mercury is injected into a rock sample at increasing pressure to determine the pore size and distribution. The measurement data is used to obtain effective porosity and absolute permeability by applying the Washburn and Katz-Thompson equations. The results show that variations in porosity and permeability values ​​are influenced by rock texture, grain size, and interpore connectivity. Rocks with a uniform pore distribution have higher permeability than rocks with poorly connected pores. Overall, the MICP method has proven effective in providing a quantitative picture of the pore microstructure and can be used to support reservoir characterization in petroleum geology studies.